2010
DOI: 10.1111/j.1467-789x.2010.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of weight loss after lifestyle interventions for overweight and obesity, a systematic review

Abstract: Lifestyle interventions can reduce body weight, but weight regain is common and may particularly occur with higher initial weight loss. If so, one may argue whether the 10% weight loss in clinical guidelines is preferable above a lower weight loss. This systematic review explores the relation between weight loss during an intervention and weight maintenance after at least 1 year of unsupervised follow-up. Twenty-two interventions (during at least 1 month) in healthy overweight Caucasians were selected and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
215
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(230 citation statements)
references
References 52 publications
8
215
0
7
Order By: Relevance
“…This superior effectiveness might be explained by the fact that these studies conducted follow-up measurements immediately after the intervention period (<6 months) as opposed to several months after the completion of the program (≄6 months) in the studies performed from a broader perspective. Systematic reviews show that (partial) weight rebound after the intervention period is common (60,61). Another explanation may be the non-randomized design of two of these three studies (ie, results may be confounded by selection bias) (40).…”
Section: Discussionmentioning
confidence: 99%
“…This superior effectiveness might be explained by the fact that these studies conducted follow-up measurements immediately after the intervention period (<6 months) as opposed to several months after the completion of the program (≄6 months) in the studies performed from a broader perspective. Systematic reviews show that (partial) weight rebound after the intervention period is common (60,61). Another explanation may be the non-randomized design of two of these three studies (ie, results may be confounded by selection bias) (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have shown that energy restriction, increased physical activity, or both can lead to successful shortterm weight loss; however, the long-term effectiveness of these interventions appears challenging (2,3). Numerous factors have been shown to influence successful weight maintenance, including behavior (4), physical activity (2), eating habits (5), the length of time an individual has maintained weight loss (6), the degree of energy deficit and consequent weight loss (3,7), and the influence of altering dietary macronutrient content (ie, carbohydrate, protein, and fat) (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors have been shown to influence successful weight maintenance, including behavior (4), physical activity (2), eating habits (5), the length of time an individual has maintained weight loss (6), the degree of energy deficit and consequent weight loss (3,7), and the influence of altering dietary macronutrient content (ie, carbohydrate, protein, and fat) (8)(9)(10)(11). It is now widely accepted that body weight and body composition are also influenced by a genetic component (which encompasses genetic polymorphisms, epigenetics, and gene transcription); however, our understanding of how these genetic determinants contribute to successful weight maintenance remains limited (12).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that there are still cohorts of patients, beyond those traditionally thought to have spiritual needs [i.e., the religious and the dying] that could benefit from spiritual care provision (Velosa et al 2017). Indeed spiritual and religious care practices have been identified across large studies as having a positive impact on reduction of alcohol intake (Barte et al 2010). Similarly unique in approach is Patel et al (Patel et al 2017) study reporting on an evaluation of a three-month feasibility study testing a UK Christian-based intuitive-eating programme in a church (n = 18).…”
Section: Differing Perspectives Spiritual Carementioning
confidence: 99%
“…Intuitive eating is implicitly spiritual in the broadest sense (Egan et al 2011) given its focus on increased awareness. It is an excellent alternative to simply dieting by reducing intake, which mostly fails (Barte et al 2010), and this intervention takes a salutogenic approach focusing on Christian wellness principals. Further, as a 'train the trainer' approach, the intervention empowers community to become involved in health promotion as opposed to a programme that is facilitated solely by healthcare professionals.…”
Section: Differing Perspectives Spiritual Carementioning
confidence: 99%